2021
DOI: 10.1111/mcn.13238
|View full text |Cite
|
Sign up to set email alerts
|

Gestational weight gain and pregnancy outcomes: Findings from North Indian pregnancy cohort

Abstract: Despite the high prevalence of inadequate gestational weight gain (GWG) and adverse pregnancy outcomes, very few studies have addressed the association between GWG and pregnancy outcomes in South Asia. Our objectives were to estimate the prevalence of GWG during the second and third trimesters within, below and above the Institute of Medicine (IOM) guidelines, and to estimate the effect of the rate and adequacy of GWG on gestational age at the time of delivery, weight, length, length‐for‐age z‐score (LAZ), wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
2
2
0
Order By: Relevance
“…Similar to our results, Goldstein et al (2017b) in a systematic review and meta-analysis that investigated the association between GWG and maternal and infant outcomes observed that inadequate GWG, whether below or above the IOM recommendations, is associated with adverse outcomes. Similar ndings were reported in other studies (Athukorala et al, 2010b;Chowdhury et al, 2022;Truong et al, 2015b). The issue of prematurity deserves special attention, as women with premature babies have less time to gain weight during pregnancy, which may indicate reverse causality in the association between GWG and prematurity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar to our results, Goldstein et al (2017b) in a systematic review and meta-analysis that investigated the association between GWG and maternal and infant outcomes observed that inadequate GWG, whether below or above the IOM recommendations, is associated with adverse outcomes. Similar ndings were reported in other studies (Athukorala et al, 2010b;Chowdhury et al, 2022;Truong et al, 2015b). The issue of prematurity deserves special attention, as women with premature babies have less time to gain weight during pregnancy, which may indicate reverse causality in the association between GWG and prematurity.…”
Section: Discussionsupporting
confidence: 92%
“…These ndings corroborate previous studies that also found associations between GWG below and above the recommendations and adverse outcomes, indicating that inadequate GWG can have negative effects on the health of the fetus and newborn [14,[27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Discussionsupporting
confidence: 90%
“…Excessive GWG is associated with an increased risk of gestational diabetes, gestational hypertension, preeclampsia, preterm birth, cesarean delivery, macrosomia, infant mortality, postpartum weight retention, and childhood obesity ( 8 12 ). Recent reports indicate a high prevalence of inadequate gestational weight gain in South Asia, in particular in India ( 13 , 14 ). Appropriate GWG is usually evaluated in comparison to two international standards – those of the Institute of Medicine (IOM) and International Fetal and Newborn Growth-21st (Intergrowth-21st) ( 9 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…This study selected healthy women who were at low risk of adverse maternal and perinatal outcomes and provided centiles of GWG for each week of gestation. In India, maternal malnutrition is highly prevalent ( 28 ) and there is a high burden of inadequate GWG ( 13 ). Despite these challenges, and the association between GWG and optimal fetal growth, there are only few studies in Asia that have explored weight gain in different trimesters of pregnancy and compared against global references (Intergrowth-21st) ( 2 , 29 ).…”
Section: Introductionmentioning
confidence: 99%